2014
DOI: 10.1128/jvi.00931-14
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma-Associated Herpesvirus ORF45 Mediates Transcriptional Activation of the HIV-1 Long Terminal Repeat via RSK2

Abstract: Robust activation of human immunodeficiency virus type 1 (HIV-1) gene expression occurs upon superinfection with Kaposi's sarcoma-associated herpesvirus (KSHV), a common AIDS-associated pathogen. Though the mechanisms underlying this phenotype remain unknown, several KSHV-encoded factors have been reported to stimulate HIV-1 long terminal repeat (LTR) activity. Here, we systematically evaluated the ability of KSHV tegument proteins to modulate the activation of an integrated HIV-1 LTR and revealed that the mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…ERK and RSK have been shown to be involved in transcriptional regulation by phosphorylation of transcription factors, histones, and histone-modifying enzymes (32). Furthermore, a role for ORF45 in transcriptional regulation is supported by the recent report from Glaunsinger's group that ORF45 potently increases HIV long terminal repeat (LTR) transcription activity in an RSK2-dependent manner (47). Because of its role in transcriptional and translational regulation, ORF45 could have a broad impact on the expression of not only viral but also cellular genes.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…ERK and RSK have been shown to be involved in transcriptional regulation by phosphorylation of transcription factors, histones, and histone-modifying enzymes (32). Furthermore, a role for ORF45 in transcriptional regulation is supported by the recent report from Glaunsinger's group that ORF45 potently increases HIV long terminal repeat (LTR) transcription activity in an RSK2-dependent manner (47). Because of its role in transcriptional and translational regulation, ORF45 could have a broad impact on the expression of not only viral but also cellular genes.…”
Section: Discussionmentioning
confidence: 50%
“…Second, as mentioned above, ORF45-mediated activation of RSK is involved in the direct interaction between KSHV and HIV-1, which is well known to drastically increase both the incidence and severity of KS. ORF45 has been shown to work synergistically with the HIV-1-encoded protein Tat to potently increase LTR transcription activity in an RSK-dependent manner (47,54). Conversely, Tat has been found to increase KSHV lytic gene expression and infectivity (55)(56)(57).…”
Section: Discussionmentioning
confidence: 99%
“…During KSHV lytic replication in either primary infection or reactivation, transient ERK activation induced by viral particles, 12-O-tetradecanoylphorbol-13-acetate (TPA), or another stimulus activates IE expression and initiates lytic replication (11,(35)(36)(37); however, ORF45-null KSHV and an ORF45-F66A point mutant (which are deficient in sustained ERK-p90 ribosomal S6 kinase [RSK] activation) exhibit reduced lytic gene expression and progeny virion production (31,38,39), suggesting that sustained ERK-RSK activation is essential for late viral transcription. In fact, a recent study showed that ORF45 directly increases the recruitment of RNA polymerase II and enhances transcription through RSK2 (40), indicating that ORF45-RSK2 promotes late transcription.…”
mentioning
confidence: 99%
“…More importantly, KSHV ORF45 has also been shown to cause persistent activation of the extracellular regulated kinase (ERK) and p90 ribosomal S6 kinases (RSKs) (13,14). This activity is important not only for virus-host interactions (15,16), but also for virusvirus interaction between KSHV and HIV (17,18).…”
mentioning
confidence: 99%